2008
DOI: 10.1080/14647270802302629
|View full text |Cite
|
Sign up to set email alerts
|

Elective Single Embryo Transfer: Guidelines for Practice British Fertility Society and Association of Clinical Embryologists

Abstract: Assisted conception treatment is the single most important cause in the increase in multiple pregnancy and births over the last 25 years. Multiple births are associated with significant peri natal morbidity and mortality. Europe has led the way in reducing multiple births by widespread adoption of an elective single embryo policy, which in Belgium is linked to an increase in state funding. Randomized controlled trials suggest that an eSET policy must include the ability to cryopreserve and transfer any remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(129 citation statements)
references
References 87 publications
2
120
0
7
Order By: Relevance
“…5 In 2008, the British Fertility Society, in conjunction with the Association of Clinical Embryologists, introduced guidelines for eSET in the UK that aimed to reduce IVF multiple pregnancy rates to less than 10%. 6 Meta-analyses have shown that in a selected population, compared with double embryo transfer (DET), eSET could reduce multiple pregnancy rates significantly, without compromising cumulative pregnancy rates. 7,8 Our centre offered eSET to eligible women in order to reduce the multiple pregnancy rate.…”
Section: P>005)。mentioning
confidence: 99%
“…5 In 2008, the British Fertility Society, in conjunction with the Association of Clinical Embryologists, introduced guidelines for eSET in the UK that aimed to reduce IVF multiple pregnancy rates to less than 10%. 6 Meta-analyses have shown that in a selected population, compared with double embryo transfer (DET), eSET could reduce multiple pregnancy rates significantly, without compromising cumulative pregnancy rates. 7,8 Our centre offered eSET to eligible women in order to reduce the multiple pregnancy rate.…”
Section: P>005)。mentioning
confidence: 99%
“…Por lo tanto, uno de los grandes desafíos es reducir la frecuencia de multigestación 10 . Es por eso que las sociedades médicas de países desarrollados abogan por la transferencia de uno o dos embriones, de acuerdo a la edad de la paciente y los resultados anteriores [11][12][13][14][15][16] .…”
Section: Discussionunclassified
“…35,36 Selection of embryos by extended in vitro culture to the blastocyst stage has received much attention, [37][38][39] and a Cochrane review, 39 and was one approach suggested in the ACE/BFS guidelines. 11 Invasive pre-implantation genetic screening has been advocated as a potential approach and is available clinically. 40 However, there is little evidence for its effectiveness in increasing treatment outcomes and, in contrast, recent prospective RCTs have provided evidence that the invasive nature of the embryo biopsy procedure may be detrimental.…”
Section: Embryo Selection For Esetmentioning
confidence: 99%
“…Grading systems differ between centres and there is a clear need for a unified, quality-assessed scoring system to allow intercentre collation of data. 11 In the present dataset, with nominally equivalent grading schemes across the centres (see Chapter 4, Data extraction and cleaning), it was necessary to normalise the grades between centres. This process is non-trivial and inexact, requiring rather strong assumptions.…”
Section: Embryo Assessmentsmentioning
confidence: 99%